Intraoperative Endoscopy as Guidance for Adequate Myotomy in Laparoscopic Heller Procedure: A Rare Case Report - Fuadi, Ahmad Fathi; Mahfuddin, Ahmad Za'im Muhtar (Diponegoro International Medical Journal, 2023)
Background: Esophageal achalasia is a rare disorder characterized by the absence of lower esophageal sphincter (LES) relaxation. The cardinal symptom is progressive dysphagia. Laparoscopic Heller myotomy (LHM) for achalasia offers long-term symptom improvement. However, there is no precise length or landmark for adequate myotomy. The intraoperative endoscopy has been proposed as a tool to measure the adequacy of the myotomy. To the best of our knowledge, there is no previous report of intraoperative endoscopy during LHM in Indonesia.Case Presentation: A 30-year-old female patient complained of progressive dysphagia and major weight loss due to esophageal achalasia for the last two months. She underwent LHM after a week of preoperative nutritional support. The endoscopic was conducted after the myotomy to ensure the adequacy of the myotomy and prevent excessive myotomy.Conclusion: The use of intraoperative endoscopy offers many advantages for LHM. It ensures adequate myotomy, thereby minimizing the risk of repeat or additional procedures. Moreover, endoscopy can help identify mucosal perforation. We propose using an intraoperative endoscopy as a routine procedure for LHM.